Assessment of Therapeutic Response to Statin Therapy in Patients With Intracranial or Extracranial Carotid Atherosclerosis by Vessel Wall MRI: A Systematic Review and Updated Meta-Analysis - Zhou, Pengyu; Wang, Yuting; Sun, Jie; Yu, Yannan; Mossa-Basha, Mahmud; Zhu, Chengcheng (Frontiers in Cardiovascular Medicine, 2021)
Background and aims: Statin therapy is an essential component of cardiovascular preventive care. In recent years, various vessel wall MRI (VW-MRI) techniques have been used to monitor atherosclerosis progression or regression in patients with extracranial or intracranial large-artery atherosclerosis. We aimed to perform a systematic review and meta-analysis on the effects of statin therapy on plaque evolution as assessed by VW-MRI. Materials and methods: Prospective studies investigating carotid and intracranial atherosclerotic plaques in patients on statin therapy monitored by serial VW-MRI were systematically identified in the literature. The plaque burden and lipid rich necrotic core (LRNC) volume of carotid plaque and the imaging features of intracranial plaques were extracted and summarized. For studies investigating carotid artery wall volume and LRNC volume, combined estimates were derived by meta-analysis. Results: Twenty-one studies of carotid plaque and two studies of intracranial plaque were identified. Sixteen studies investigating carotid plaques that included 780 patients by High-resolution VW-MRI were included in the meta-analysis. There was no significant change in carotid wall volume from baseline to 12 months. A significant change in LRNC volume was observed at >12 months compared to baseline (Effect=-10.69, 95% CI=-19.11, -2.28, P<0.01), while no significant change in LRNC volume at 3-6 months or at 7-12 months after statin therapy initiation in 6 studies. Increases in fibrous tissue and calcium and reduction in neovascularization density of the plaque were seen in 2/3 studies (including 48/59 patients), 1/3 studies (including 17/54 patients), and 2/2 studies (including 71 patients) after statin therapy, respectively. Two studies with 257 patients in intracranial atherosclerosis showed that statins could effectively decrease wall volume and plaque enhancement volume. Conclusions: Collective data indicate that statins could potentially stabilize carotid plaques by significantly reducing LRNC with 1 year of therapy as shown on serial carotid VW-MRI. There was no significant decrease in wall volume, however, indicating that plaque composition changes might be more sensitive to response monitoring than wall volume. It is likely that more sensitive, clinically relevant, and preferably quantitative indicators of therapeutic effects on intracranial vessel plaque morphology will develop in the future.